2020
DOI: 10.11604/pamj.2020.37.302.20521
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological, clinical and biological profile of neuromeningeal cryptococcosis among people living with in Kinshasa, Democratic Republic of Congo

Abstract: Neuromeningeal cryptococcosis (NMC) is one of the most frequent opportunistic infections (OI) in Human Immunodeficiency Virus (HIV) infection. In Kinshasa, the latest data on cryptococcosis were published in 1996. The objective was to describe the epidemiological, clinical and biological profiles of NMC in HIV-infected people living in Kinshasa. This is a descriptive study based on the medical records of patients who attended three clinics in Kinshasa between January 1 s t 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 5 publications
(7 reference statements)
0
7
2
Order By: Relevance
“…In our study, the lethality was 43.5%. This lethality is greater than those reported in Kinshasa (34.8%) 19 and Bobo Dioulasso (27.8%), 26 but lower than those observed in other African series (from 71.1% to 83.3%). 32,36,37 These data clearly show the value of early management of patients with NMC.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…In our study, the lethality was 43.5%. This lethality is greater than those reported in Kinshasa (34.8%) 19 and Bobo Dioulasso (27.8%), 26 but lower than those observed in other African series (from 71.1% to 83.3%). 32,36,37 These data clearly show the value of early management of patients with NMC.…”
Section: Discussioncontrasting
confidence: 60%
“…Our rate is lower than those of studies carried out in other African countries ranging from 5.6% to 11.43%. [17][18][19][20][21] Two Ivorian studies conducted by Kadjo et al 22,23 had noted a prevalence of 0.6 and 1.1%. These authors found that in ten years, the frequency of this disease has almost halved.…”
Section: Discussion Prevalencementioning
confidence: 99%
See 2 more Smart Citations
“…In this HIV population at high risk of cryptococcosis, we include PLHIV in treatment failure and those on ART but lost to follow-up. Thus, in Kinshasa, the prevalence of NMC has previously been estimated at 8.8%, with a mortality rate of one in three patients [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%